An Investigation of Communication in Virtual High Schools - Belair, Marley (International Review of Research in Open and Distributed Learning, 2012)
Virtual schooling is an increasing trend for secondary education. Research of the communication practices in virtual schools has provided a myriad of suggestions for virtual school policies. The purpose of this qualitative study was to investigate the activities and processes involved in the daily rituals of virtual school teachers and learners with the goal of determining how regular phone calls by teachers contributed to the work habits of students. Eight virtual teachers were observed attempting to contact more than 60 struggling learners. Phone conversations with 12 of these learners showed that teachers repeatedly attempted to help them. Eleven students were interviewed and indicated preferences for written communications. Ten additional teachers who were interviewed emphasized the difficulty they had in reaching students by phone and the lack of student responses to phone-call attempts. The teachers in the study provided additional data regarding their regular communication patterns. Archival records from more than 100 contact attempts showed that approximately 20% of the students responded to teacher phone calls and less than half of these students completed the work requested. The interview data revealed that teachers believe written communications or multiple forms of communication may be more effective than regular phone calls. Future research should extend current research by expanding on sample size and investigating alternate methods of communication. Further investigation of learner responses to phone calls and of nonresponsive students could add to this data.